(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: There are several indications for performing the caesarean section. Objective: The purpose of the present study was to see indication of operations and pattern of referral among women presented with post-caesarean section complications. Methodology: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecological at Dhaka Medical College and Hospital, Dhaka, Bangladesh from January 2013 to June 2013 for a period of six months. All women admitted with post caesarean section complications referred from different level of hospitals with the age group of more than or equal to 18 years were included as study population. All relevant data were recorded in a predesigned data collection sheet which included pattern of referral, causes of referral and history of primary operation. Results: A total number of 50 women were included in this study. Maximum (40%) patients were within the age group of 21 to 25 years. For majority caesarean delivery were done for prolonged labor (24.0%) followed by previous one or two caesarean section (16.0%). However, obstructed labour and postdated pregnancy were also reported which were 6(12.0%) cases in each. Maximum cases of CS were performed by practicing doctors (46%). About 48.0% patients came with referral notes from the referring hospitals and majority (52%) were referred without any referral notes. Conclusion: In conclusion the most common indication for referral of women presented with post-caesarean section complications has been performed by practicing doctor for prolonged labor without referral notes in the advice. Journal of National Institute of Neurosciences Bangladesh, July 2024;10(2):119-123